Prepubertal plaque discoid lupus erythematosus. - Ingravallo, G.; Garofalo, L. (European Journal of Pediatric Dermatology, 2022)
Discoid lupus erythematosus (LED) is rare in children. In the prepubertal period, the classic signs of follicular hyperkeratosis and atrophy may be missing. We describe a case of LED with erythematous plaques in an 8-year-old child and review 3 other similar cases observed in the last 8 years.